Inclusive STEM education: bridging gaps, empowering autism community through aquaponics for a sustainable future / Suzi Seroja Sarnin ... [et al.]. - Sarnin, Suzi Seroja; Md Tan, Mohd Nor; Dohad, Mohd Rizal; Ishak, Norlela; Abu Bakar, Raudah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In Malaysia, the autism community faces substantial barriers in accessing Science, Technology, Engineering, and Mathematics (STEM) education-fields that are pivotal for driving innovation and economic growth. As of December 31st, 2021, there were 40,743 registered individuals with autism in the country, encompassing both adults and children. By 2022, the Department of Social Welfare Malaysia reported an increase to 42,349 registered individuals with autism. Alarmingly, the unemployment rate among the autism population exceeds 70%, underscoring a critical gap in workforce participation and inclusion. Traditional educational frameworks predominantly rely on standardized teaching methods that may not cater to the diverse needs of students with autism. This challenge is compounded by a lack of access to specialized assistive technologies, such as customized learning platforms and sensory-friendly tools, as well as a shortage of educators trained to effectively teach students with autism. Consequently, many individuals with autism are excluded from equitable participation in STEM education, limiting their ability to acquire the skills essential for contributing to national development.